2019
DOI: 10.21203/rs.2.15338/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors of pulmonary complications after minimally invasive surgery for elderly patients with vertebral compression fractures

Abstract: Purpose: To determine the risk factors for pulmonary complications after minimally invasive surgery in elderly patients with vertebral compression fractures (VCFs). Methods: We retrospectively analyzed 233 elderly patients (age ≥ 65 years) with VCFs who underwent percutaneous vertebroplasty (PVP) or percutaneous kyphoplasty (PKP) surgery at Hebei General Hospital from January 2011 to December 2016 . Risk factors and the effects of the model were determined by univariate logistic regression analyses and the rec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In elderly patients with hypertension, the occurrence of complications following a hip fracture signi cantly increases the risk of acute heart failure. Particularly in the respiratory system, common postfracture pulmonary complications such as pneumonia and pulmonary embolism can cause hypoxemia and increased cardiac stress, further burdening the already strained heart due to hypertension 29 . Digestive system complications, such as gastric ulcers and gastrointestinal bleeding, may be exacerbated by the prolonged bed rest and use of analgesics necessary after hip surgery, leading to reduced blood volume and altered cardiac preload 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In elderly patients with hypertension, the occurrence of complications following a hip fracture signi cantly increases the risk of acute heart failure. Particularly in the respiratory system, common postfracture pulmonary complications such as pneumonia and pulmonary embolism can cause hypoxemia and increased cardiac stress, further burdening the already strained heart due to hypertension 29 . Digestive system complications, such as gastric ulcers and gastrointestinal bleeding, may be exacerbated by the prolonged bed rest and use of analgesics necessary after hip surgery, leading to reduced blood volume and altered cardiac preload 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that, in osteoporotic thoracolumbar burst fracture, the decrease in the height of the anterior and posterior edges of the vertebral body, fractures of different degrees in the posterior wall of the vertebral body, and vertebral cortical defect, all appeared to be risk factors of cement leakage (11). Additionally, some scholars consider that it is easy to make fracture segments shift into the spinal canal and leak cement along the cortex behind the ruptured vertebral body by percutaneous kyphoplasty (12)(13)(14). Hence, osteoporotic patients with thoracolumbar burst fractures have been regarded as a contraindication for the treatment of percutaneous kyphoplasty.…”
mentioning
confidence: 99%